3D printable conductive materials for the fabrication of electrochemical sensors: A mini review - Hamzah, Hairul Hisham; Shafiee, Saiful 'Arifin; Abdalla, Aya; Patel, Bhavik Anil (Elsevier, 2018)
The review presents recent developments in the use of conductive materials that can be printed using additive manufacturing (3D printing), enabling the development of mass-produced electrochemical sensors of varying geometries. This review will highlight some key electroanalytical applications of 3D-printed electrochemical sensors and discuss their potential future capabilities.